Pengaruh Insentif, Budaya Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Badan Pengelola Pajak dan Retribuasi Daerah - Sri Rezeki; Kesli Betty Sinurat; Habib Futut Santoso R; Muhammad Irwan; Mutiara Ferdina Arisandi Manullang; T. Ahmad Helmi (Journal of Business and Economics Research (JBE), 2022)
This study aims to determine how much influence additional employee income, work discipline, work environment, together and partially on performance. The research variables are additional employee income (X1), work discipline (X2), work environment (X3), and performance (Y). Methods of collecting data through surveys and distributing questionnaires. The analytical method used is validity and reliability test, multiple regression analysis, to test the hypothesis used t test and F test. From the results of the regression analysis, the equation Y = 9.444 + 0.173X1 + 0.500X2 + 0.196X3, then based on the partial test (t test) obtained: (a) additional employee income has a positive and significant effect on performance. (b) work discipline has a positive and significant effect on performance. (c) the work environment has a positive and significant effect on performance. Then based on the joint hypothesis test (Test F) it can be seen that additional employee income, work discipline, and work environment have a positive and significant effect on performance. And based on the coefficient of determination test (R2), which is 0.644 or 64.4%, this shows that the percentage contribution of the additional variable of employee income, work discipline, and work environment to the performance variable shows the effect and the rest is influenced by other variables.